ChemInform Abstract: Synthesis of C‐2 Arylated Tryptophan Amino Acids and Related Compounds Through Palladium‐Catalyzed C—H Activation. Issue 1 (7th January 2014) - Preciado, Sara; Mendive‐Tapia, Lorena; Albericio, Fernando; Lavilla, Rodolfo
Abstract This simple, mild, and versatile method allows the preparation of α‐arylated indoles including amino acid derivatives directly from the corresponding indole or amino acid precursors.